The Effect of Knowledge Management, Employee Engagement, and Intrinsic Motivation on Employee Performance with Organizational Culture as a Moderating Variable - Abdul Muslim; Luhut Indra; Hara Ibnufauzi Lystiardi; Sarfilianty Anggiani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to obtain an overview of how the influence of knowledge management, employee involvement, and intrinsic motivation is moderated by organizational culture on employee performance. This study uses an associative quantitative approach using regression techniques. The sample of this study amounted to 199 people where the majority consisted of employees engaged in services (46.7%) and trade & manufacturing (22.1%). Research data was collected through a questionnaire instrument designed using a Likert scale which was first tested for validity and reliability. Based on the research results, there is a positive and significant influence of knowledge management and intrinsic motivation on employee performance. Otherwise, there is no positive and significant effect of employee engagement on employee performance. Meanwhile, organizational culture cannot be used as a moderating variable to improve employee performance because of the dominance of this variable on employee performance. This finding shows that if an organization wants to improve the performance of its employees, it can be done by implementing optimal knowledge management and providing consistent intrinsic motivation.